Soil Liquefaction Potential in Different Seismic Zones of Bihar, India - Thakur, I. C.; Roy, L. B. (Engineering, Technology & Applied Science Research, 2022)
Liquefaction potential analysis for the liquefiable as well as non-liquefiable soils of Bihar state has been performed in this paper based on the actual field data from three seismic zones, i.e. zone III, zone IV, and zone V. The analysis has been performed following the simplified procedure given in [1] and later modified in [2]. The results show that districts under seismic zone III are comparatively more resistant to liquefaction in most cases, districts of zone IV are relatively more prone to liquefaction up to a few depths, and districts of zone V are most liquefiable. Liquefaction resistance is primarily depending upon the fine content of soil and SPT N-values.